SISTEM KEAMANAN PELACAKAN KENDARAAN BERMOTOR MENGGUNAKAN RASPBERRY PI 3 DENGAN MODULE GPS SECARA REALTIME BERBASIS WEB - Muksan SAN Junaidi (SIMETRIS, 2020)
Motor vehicle theft is a criminal problem that very often occurs in the community. Along with the development of technology and the level of demand for motor vehicle safety in the community that begins to increase. One of the devices that has been developed is Internet of Things (IoT) technology which is able to connect and facilitate the communication process between machines, devices and humans via the internet network. The purpose of this research is to develop a monitoring application that utilizes IoT technology as a medium for tracking the location of motorized vehicles. This research consists of 3 main system components, including the End Device System found on the Raspberry Pi device, Web Service (Back-End System) as a service for data transfer, and Front-End System user interface in the form of a website application. This system has several main features, including realtime tracking and is equipped with an activity log which can be used to determine the identity of the vehicle user. Users can access these features through the application from the website. Based on the trials conducted, this system works well on motorized vehicles, however, this system has more dependence on the internet network available in each region.